2015
DOI: 10.1136/gutjnl-2015-309460
|View full text |Cite
|
Sign up to set email alerts
|

Psychological comorbidity increases the risk for postinfectious IBS partly by enhanced susceptibility to develop infectious gastroenteritis

Abstract: (ClinicalTrials.gov NCT01497847).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 39 publications
6
60
2
1
Order By: Relevance
“…Wouters and colleagues investigated a cohort of over 18 000 people exposed to contaminated drinking water, finding that pre-existing anxiety and somatisation were linked to a lower immune response and a greater risk of developing GI infection 33. In this respect, psychological disorder may be viewed as a predisposing factor for infection, which in turn is postulated as a cause of IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Wouters and colleagues investigated a cohort of over 18 000 people exposed to contaminated drinking water, finding that pre-existing anxiety and somatisation were linked to a lower immune response and a greater risk of developing GI infection 33. In this respect, psychological disorder may be viewed as a predisposing factor for infection, which in turn is postulated as a cause of IBS.…”
Section: Discussionmentioning
confidence: 99%
“…A Turkish case-control study (33) showed that depression among IBS cases was significantly much higher (38%) than among the controls (4%). Another recent study from Belgium reported an increased risk of patients with psychological co-morbidity to develop postinfectious IBS (PI-IBS) (34). Medical students represent a unique stress-heavy lifestyle model, consisting of long hours of focused physical and cognitive activity under significant social-competitive pressure (3,24).…”
Section:  Psychological and Psychiatric Factors (Stress Anxiety Anmentioning
confidence: 99%
“…When Wouters et al [55] explored risk factors for post-infectious IBS (PI-IBS) in a large cohort of subjects exposed to drinking water contaminated with GI pathogens (e.g., norovirus, Giardia lamblia , and Campylobacter jejuni ), the risk of developing symptoms consistent with a FGID was higher in subjects with pre-existing anxiety, as well as in younger individuals. The authors also observed an inverse link between anxiety scores and CD4-positive T-lymphocytes expressing interleukin (IL)-2.…”
Section: Evidence For the Role Of Infections In Fgidmentioning
confidence: 99%